Biosynthesis of Chiral Poly-Hydroxyacyl Esters and their Enzymatic Functionalization as Glycopolymers / Ahmad Mohammed Gumel - Gumel, Ahmad Mohammed (2013)
The use of biodegradable polymers such as polyhydroxyalkanoates (PHAs) over their non-degradable petro-chemical based counterparts is among the measures taken towards environmental friendliness and sophistication in industrial and biomedical applications. Issues such as rate of degradability and the increasing demand in specialty applications for these biopolymers, particularly in biomedical field e.g in controlling the precise target delivery of a therapeutic drug, as well as the capability of the polymeric drug carrier to release a drug at an independent time scale warrant an intense research in the processes for biopolymer production, functionalization and modification. Although several approaches in devising simpler and cost effective means to improve the desirable traits (e.g. degradability, molecular wieght, crytallinity etc) of these biodegradable polymers have been reported, which include chemical synthesis and blending, wider options need to be explored. In this research, a mild and environmental-friendly process for the biosynthetic preparation of PHA was investigated. In the in vitro enzymatic PHA biosynthesis, a sonication process enhanced the rate of polymer propagation by more than two-fold, while the enzymatic turnover number increases by 3 times. In addition, the polymer properties viz molecular weight, crystallinity and polydispersity were improved under sonication as compared to the non-sonicated process. The in vivo PHA production by bacterial fermentation utilizes renewable carbon substrates. The process was observed to be growth associated, resulting in PHA accumulation of about 50 to 77% (w/w) and PHA yields ranging from 10. g L-1 to 15.5 g L-1, respectively. The type and compositon of accumulated PHA depend on the type of carbon source fed and the bacterial species. For example, feeding fatty acids from octanoic acid (C8:0) to oleic acid (C18:1) as sole carbon and energy source in the newly isolated strain of Pseudomonas putida Bet001, as much as 50 to 69% of the microbial dry mass PHA accumulation with a molecular weight ranging from 56 to 78 kDa was observed. On the other iv hand, another new bacterial isolate Delftia tsuruhatensis Bet002, failed to use medium-chainlength fatty acids i.e. C8 to C10 for growth and PHA accumulation. When the bacterium was fed with C14:0 to C18:0 fatty acids, a homopolymer of poly-3-hydroxybutyrate (PHB) accumulation was observed. When the bacterium was supplied with unsaturated oleic acid (C18:1), a copolymer containing C4 to C10 acids with both even and odd carbon atom monomers is accumulated. As in P. putida Bet001, PHA accumulation for D. tsuruhatensis Bet002 is also growth associated with PHA yield of about 45 to 77% on cell dry weight basis and a molecular weight ranging from 131 to 199 kDa. Independent of the species, the type of carbon source influences both the thermal stability and crystallinity of the PHA. With the aim to improve the degradability of these important polymers and possibly expanding their niche applications, the PHA was conjugated with sugar moieties via enzyme catalysis. Besides showing better compostability, the biodegradability of the functionalized glycopolymers increase by factor of 1.5 compared to the non-functionalized materials. They showed an improved thermal stability with highest melting and thermal degradation temperatures of 150oC and above 300oC, respectively. The functionalization reaction afforded a glycopolymer with an average molecular weight (Mw) of 1.7 to 16.8 (±0.2) kDa depending on the solvent polarity. As such, controlling the binary solvent mixtures as reaction media, enables to influence and/or manipulate the rate of product formation and reaction stability resulting in higher efficiency and yield. The polymer functionalization with sugar moieties was carried out via a simple, single-step enzymatic catalysis, which is specific, viable and environmental-friendly.